Total hip replacement in a patient with contralateral hemipelvectomy: a case report - Caicedo Mazabel , Pablo Andrés; Gaitán-Lee, Hernando; Guzmán Nalus, Felipe; Sardi Barona, Leon Alberto (International Journal of Research in Orthopaedics, 2023)
Total hip arthroplasty is one of the most frequently performed surgeries today with excellent clinical and functional results for patients with advanced stages of hip osteoarthritis. Performing this surgical procedure in patients with a history of lower limb amputation is rare, so some important considerations must be taken for surgical planning, positioning on the operating table, and rehabilitation. There are very few case reports described in the literature. We present the case of a patient with symptomatic stage III Tonnis hip osteoarthritis and a history of contralateral external hemipelvectomy, who underwent total hip replacement. Preoperative planning, surgical technique, and 6-year follow-up are described.